2021
DOI: 10.1177/17562848211047130
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut mycobiome in health and diseases

Abstract: The gut microbiome comprised of microbes from multiple kingdoms, including bacteria, fungi, and viruses. Emerging evidence suggests that the intestinal fungi (the gut “mycobiome”) play an important role in host immunity and inflammation. Advances in next generation sequencing methods to study the fungi in fecal samples and mucosa tissues have expanded our understanding of gut fungi in intestinal homeostasis and systemic immunity in health and their contribution to different human diseases. In this review, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 179 publications
(301 reference statements)
2
46
0
Order By: Relevance
“…Alterations in the gut bacterial microbiota structure have been well studied in metabolic diseases such as gestational diabetes mellitus (GDM) ( Wu et al, 2021 ), type 2 diabetes ( Bielka et al, 2022 ) and obesity ( Turnbaugh et al, 2009 ), and an increasing number of reports suggest that gut commensal fungi, as an important component of the intestinal microbiome, also influence host metabolic homeostasis ( Shah et al, 2021 ; Zhang et al, 2021 ). Recent studies indicate that commensal fungi have the potential to influence host metabolism directly.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the gut bacterial microbiota structure have been well studied in metabolic diseases such as gestational diabetes mellitus (GDM) ( Wu et al, 2021 ), type 2 diabetes ( Bielka et al, 2022 ) and obesity ( Turnbaugh et al, 2009 ), and an increasing number of reports suggest that gut commensal fungi, as an important component of the intestinal microbiome, also influence host metabolic homeostasis ( Shah et al, 2021 ; Zhang et al, 2021 ). Recent studies indicate that commensal fungi have the potential to influence host metabolism directly.…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence that non-bacteria gut microorganisms play a role in cancer pathogenesis as well. Recent research has indicated that bacteria, viruses, and/or fungi were widespread in malignancies, played critical actors in cancer immunotherapy, and could be manipulated to reduce the incidence of metastases ( Coker et al., 2019 ; Hakozaki et al., 2020 ; Zhang L. et al., 2021 ; He et al., 2021 ). Our study also found various bacteriophages in NSCLC patients, which indicated that other non-bacteria gut microorganisms like virus may be important in gut homeostasis in disease states.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of ITS and18S rRNA sequencing could provide a more comprehensive characterization of intestinal fungi ( 216 ). It should be noted that intestinal fungal studies that utilize metagenomics and metatranscriptomic analysis are limited till now ( 217 ). In addition, as an important turning point in microbiota research, newly-developed culture-dependent strategies, such as high-throughput culturomics combined with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) and ITS sequencing, make up for the deficiency of sequencing research and has been applied in fungal microbiota research ( 218 ).…”
Section: Prospectivesmentioning
confidence: 99%